Pemberdayaan Masyarakat melalui Program Sutera Emas (Studi pada Inovasi Pelayanan Kesehatan di Puskesmas Kepanjen, Kabupaten Malang) - Ilmi Usrotin Choiriyah (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2016)
The purpose of this study was to determine and analyze the concept of health service innovation through sutera emas programs in the Kepanjen Clinic, Malang Regency; process of community empowerment, benefits of community empowerment; as well as supporting and inhibiting factors in community empowerment through sutera emas program. Methods research used a qualitative approach with descriptive research. Informants in this study included sutera emas cadre, village midwife, clinic personnel, Malang District Health Department officials, and local community. The results showed the concept of sutera emas program was undertaken by community as a key informant to the medics that was linked through via sms, then be processed through sutera emas software applications. The process of community empowerment through sutera emas programs performed on the awareness and behavior stages, it is related to the establishment of clean and healthy living and capacity stages through transfer of knowledge and science to the community that has been done by socialization and training to the sutera emas cadres. Benefits of community empowerment through sutera emas programs namely community as subject and object on the empowerment that served as key informants in its program implementation. Supporting factor in this community empowerment included cooperation and coordination among the stakeholders involved, commitment from local governments, as well as the enthusiasm society. Meanwhile, the inhibiting factor included low quality of human resources, lack of funds and lack of public awareness for healthy living.